2018
DOI: 10.1016/j.japh.2018.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of a randomized trial evaluating two approaches for promoting pharmacy-based referrals to the tobacco quitline

Abstract: Brief cessation interventions are feasible in community pharmacies, and the 2 approaches evaluated for engaging pharmacy personnel were similarly effective and collectively led to meaningful increases in the number and proportion of all patients who called the quitline. Involvement of community pharmacy personnel in tobacco cessation presents a significant opportunity to promote quitline services by connecting patients with an effective publicly available resource.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 36 publications
(41 reference statements)
2
10
0
Order By: Relevance
“…With regards to the latter, the white paper notes, “…support personnel can also assist with scheduling and communicating referrals to other health care providers.” Our findings demonstrate a need to clearly define roles for pharmacy technicians in referrals and provision of associated training. This recommendation is consistent with Hudmon et al work demonstrating success with two models (academic detailing and mailed materials) for engaging community pharmacy staff (both pharmacists and pharmacy technicians) in promoting referrals to a tobacco quitline . Clear roles and training for community pharmacists and pharmacy technicians in making quitline referrals were developed, with pharmacy technicians positioned to refer interested patients to pharmacists and the quitline for counseling .…”
Section: Discussionsupporting
confidence: 68%
“…With regards to the latter, the white paper notes, “…support personnel can also assist with scheduling and communicating referrals to other health care providers.” Our findings demonstrate a need to clearly define roles for pharmacy technicians in referrals and provision of associated training. This recommendation is consistent with Hudmon et al work demonstrating success with two models (academic detailing and mailed materials) for engaging community pharmacy staff (both pharmacists and pharmacy technicians) in promoting referrals to a tobacco quitline . Clear roles and training for community pharmacists and pharmacy technicians in making quitline referrals were developed, with pharmacy technicians positioned to refer interested patients to pharmacists and the quitline for counseling .…”
Section: Discussionsupporting
confidence: 68%
“…Previous research shows that health promotion programs, such as mass media campaigns, targeted mailings, incentive payments to clinicians, and pharmacy-led referrals can increase use of Quitline services. [15] , [16] , [17] , [18] , [19] However, the research on interventions to increase Quitline use in the Western Pacific region is limited to evaluations of Australian mass media campaigns. These studies found that mass media anti-smoking campaigns significantly increased the volume of calls to the Quitline.…”
Section: Introductionmentioning
confidence: 99%
“…This study applied a randomized design, with the community pharmacy as the unit of randomization, to estimate the impact of two intervention strategies for engaging community pharmacy personnel in referring patients who use tobacco and are interested in quitting to the tobacco quitline [19,22,23]. Quitlines are publicly funded programs available in all 50 states and US territories (1-800-QUIT NOW), offering a variety of free resources, including information on how to quit smoking, 1-on-1 telephone-based counseling, referral to other cessation resources, information on FDA-approved cessation medications, and in some cases, cessation medications provided at no cost [24].…”
Section: Methodsmentioning
confidence: 99%
“…Consistent with this, except for addressing reorders for implementation tools, the research team communicated with the study sites only during periods of data collection. Detailed aspects of the study design, including sampling procedures, recruitment results, and baseline findings, are described in detail elsewhere [19,22,23]. The study procedures and materials were approved by the Purdue University Human Research Protection Program.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation